2021
DOI: 10.1007/s11067-021-09522-z
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Concerted Strategies for Competitive and Resilient Regions

Abstract: The European space-economy represents a complex system with a great internal heterogeneity, intensive socioeconomic interactions and differential growth trajectories among countries and regions. The present study aims to investigate the connectivity between spatial competitiveness and resilience in Europe and seeks to design an operational framework for concerted strategies of competitive and resilient regions. To assess the linkage between resilience and competitiveness, we have developed a new measure, viz. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…), the continuous evolution of the regional development drivers and the efforts to find formulas for adaptation and survival (Bristow & Healy, 2015). The concept of resilience has a long tradition in biological and engineering sciences; in the last decade it also gained popularity in urban and regional sciences (Borsekova et al, 2018(Borsekova et al, , 2021Drobniak, 2018;Smętkowski, 2015). Definitions of the phenomenon of resilience can apply to man, society, ecosystem or city.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…), the continuous evolution of the regional development drivers and the efforts to find formulas for adaptation and survival (Bristow & Healy, 2015). The concept of resilience has a long tradition in biological and engineering sciences; in the last decade it also gained popularity in urban and regional sciences (Borsekova et al, 2018(Borsekova et al, , 2021Drobniak, 2018;Smętkowski, 2015). Definitions of the phenomenon of resilience can apply to man, society, ecosystem or city.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…There are two novel aspects here: resilience and crossborder integration in the case of the Polish-Czech borderland. The article was prepared using questionnaires carried out under the Project The crisis at the Turów Mine and its impact on Czech-Polish cross-border cooperation: An evaluation, conclusions and recommendations, funded by the Polish National Agency for Academic Exchange in 2022 1 . We assume that the main goal of these regions is to work towards sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent discussions of urban resiliency, along with appropriate case studies, can be found in Shearmur et al (2016) and Irwin et al (2017). In any case, introducing the ideas of resilience and vulnerability into a region's competitive strategy is becoming an increasingly popular undertaking (Borsekova et al 2021).…”
Section: Vulnerability and Resiliencymentioning
confidence: 99%
“…According to OECD (2016), resilience is the ability to absorb economic, environmental or social shocks or stresses and to accommodate and to mitigate the impact of these shocks while retaining the capacity to carry out essential functions and without passing them on to other entities. According to Borsekova et al (2021), competitiveness and resilience are two mutual concepts, as competitiveness is also perceived as an effective response to unexpected disturbances. Stanickova and Melecký (2018) also have the same school of thought as these authors too define competitiveness as the ability to withstand unexpected external shocks.…”
Section: Introductionmentioning
confidence: 99%